Identification of uncertainty sources statistical decisions when diagnosing industrial facilities - Мигущенко, Руслан Павлович (Technology audit and production reserves, 2015)
We consider probabilistic models of decision-making as part of the generalized algorithm of technical diagnostics. The existence of three sources of statistical uncertainty of decisions that affect the accuracy of diagnosis and restrictions on the number of measurement information. Developed and presented probabilistic graphical model types diagnostic reliability of dynamic objects. These studies continued to study one of the directions in the matter of building control systems and diagnostics based on a probabilistic or statistical approach. Such an approach is justified, since all parameters in the industrial objects are random and deterministic view does not allow the construction of efficient algorithms for control, diagnostics and management. Studies that are given in the article was a logical continuation of the work of the author in the field of vibration diagnostics of the state of industrial facilities.